Puberty Health Education in Iranian Teenagers: Self - Learning or Lecture and Discussion Panel ? - Zahra Mohammadzadeh*; Zahra Allame; S Shahroki; Hamidreza Oriezi; Mohammad reza Marasi (مجله ایرانی آموزش در علوم پزشکی, 2001)
Background. Teenagers, a huge age group in developing countries, face a period with many physical, mental and social problems. Appropriate health education concerning their periodic development is of importance in community health services. The present study performed a comparative assessment of subjects’ knowledge, attitude and practice, concerning puberty health programs. Method. In an interventional study, 350 girl students aged between 12 and 14 were randomly selected through a two-phase sampling and divided into two parallel groups. Their knowledge, attitude and practice concerning puberty health were measured by a questionnaire for each subject. Then, one group was trained through a self - learning pamphlet and another participated in a discussion panel and some lectures about puberty health. Mean scores were obtained by a test and compared between groups as well as in pre- and post intervention using student t-test and paired t-test. Results. Both groups were similar in scores before intervention. After intervention, mean score for knowledge significantly increased in both groups (P<0.001). In the self-learner group, mean scores for attitude were not significantly different after education (p=0.16 & 0.056, respectively) but in the other group, they were statistically remarkable (p<0.001; p=0.0001, respectively). The comparison of scores obtained in two groups showed significant increases in knowledge and practice levels through discussion panel (p<0.001) but no significant difference was observed concerning attitude (p=0.84). Conclusion. Discussion panel is more effective than self-learning despite traditional and cultural obstacles in puberty health education for Iranian teenage girls.